Jerome : his life, writings, and controversies - Kelly, J. N. D. (John Norman Davidson) (London : Gerald Duckworth & Co. ; Old Piano Factory, 1975)
xi, 353 pages ; 23 cm; Reprint. 2e imp. publ. par J.N.D. Kelly, ©1975
Keywords: Jerome, Saint, d. 419 or 420